Peningkatkan Kinerja Guru Melalui Penerapan Gaya Kepemimpinan Kepala Sekolah yang Efektif di SMA Primaganda Jombang - Mujahidin Mujahidin (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2023)
This research aims to analyze the impact of implementing an effective principal's leadership style on improving teacher performance at Primaganda High School. School principals play an important role in establishing a positive work climate, providing clear direction, and providing motivation and support to teachers. This research involves case studies in several schools as a basis for analyzing the relationship between school principal leadership styles and teacher performance. The research method used is qualitative with data collection techniques in the form of interviews, observation and documentation. These three techniques were used to collect data from teachers regarding their perceptions of the principal's leadership style and understand the deeper views of principals and teachers. This data is then analyzed to identify patterns and possible relationships between leadership styles and teacher performance. The results of this research indicate that school principals who implement effective leadership styles, such as providing ongoing support, providing clear direction, and encouraging teacher professional development, tend to have a positive influence on teacher performance. Teachers who feel strong support and direction from their principal tend to be more motivated, innovate, and produce better learning outcomes. To improve teacher performance, school principals always motivate teachers and employees. Obstacles faced by school principals in improving teacher performance through situational leadership include resistance to change, identification of teacher readiness levels and the need for appropriate time management.